2001
DOI: 10.1046/j.0007-1323.2001.01855.x
|View full text |Cite
|
Sign up to set email alerts
|

Preserved endothelial integrity and nitric oxide synthase in saphenous vein grafts harvested by a ‘no-touch’ technique

Abstract: Some of the sites with potential for nitric oxide release in vivo are removed during conventional saphenous vein harvesting. These sites were preserved after no-touch harvesting, suggesting the potential to improve coronary artery bypass graft patency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
69
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 17 publications
1
69
0
2
Order By: Relevance
“…Stretching of veins during harvesting and preparation for grafting can lead to partial loss of ECs, 34 whereas a "no touch" technique for vein harvest leads to the preservation of ECs. 35,36 Veins grafted into the arterial circulation are also exposed to a sudden increase in blood flow, which elevates shear stress at the vascular wall. Venous ECs are activated rapidly by the application of arterial shear stress, [37][38][39][40][41] and it is likely that this process contributes to early inflammatory processes in vein grafts.…”
Section: Discussionmentioning
confidence: 99%
“…Stretching of veins during harvesting and preparation for grafting can lead to partial loss of ECs, 34 whereas a "no touch" technique for vein harvest leads to the preservation of ECs. 35,36 Veins grafted into the arterial circulation are also exposed to a sudden increase in blood flow, which elevates shear stress at the vascular wall. Venous ECs are activated rapidly by the application of arterial shear stress, [37][38][39][40][41] and it is likely that this process contributes to early inflammatory processes in vein grafts.…”
Section: Discussionmentioning
confidence: 99%
“…The endothelial injury may occur owing to mechanical reason such as excesses separation, stretch and distension, as well as chemical reason such as hypoxia during preservation, ischemia-reperfusion and condition of storage solution. In previous study, prevention of mechanical injury was emphasized in protection of vein graft, including applying "no touch" and endoscopic mimimally invasive techniques, addition of vasodilator to avoid vascular spasmodism, as well as retaining extravascular tissue [3] . Thatte et al [4] have reported that endothelial cell activity of HSV was affected in several minutes of preservation and after 1 h of preservation endothelial cells phenotype changed leading to attenuating of anticoagulation, increasing of permeability and adhesion, thus endothelial cells appeared proinflammatory characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide (NO) is produced from L-arginine by nitric oxide synthase (NOS), which regulate vascular tension, sustain normal vascular physiologic function, decrease expression of adhesion molecules as well as inhibit leucocyte-endothlium interaction and platelet aggregation. Tsui et al reported that harvesting HSV by using minimally invasive techniques may preserve endothelial NOS (eNOS) expression and NO production as well [3] . In this study we found that after preservating 1 h in solution with Troglitazone, eNOS expression of HSV is significantly higher than control group, meanwhile vascular cell adhesion molecule-1(VCAM-1) and intercellular adhesion molecule-1(ICAM-1) expression of HSV is significantly lower than control group leading to conclusion that preservation solution with Troglitazone may offer better protective function to HSV.…”
Section: Discussionmentioning
confidence: 99%
“…The goal is to preserve endothelial and smooth muscle cell presence and function in the graft, with a presumed outcome of reduced maladaptive neointimal overgrowth, though early prevention of thrombosis is also a rationale. Endothelial preservation will maintain nitric oxide and prostacyclin generation, 21 critical factors for sustaining function, patency, and vascular integrity. The effect of no-touch graft harvesting on subsequent bypass surgery outcome is difficult to evaluate, given that it represents differences in personal surgical technique and that endothelial cells cannot be directly seen or tracked following clinical graft placement.…”
Section: Graft Ec Integritymentioning
confidence: 99%
“…Many vascular surgeons advocate a "no touch" technique [19][20][21] for vein graft harvest, in an effort to minimize vein graft iatrogenic injury. The goal is to preserve endothelial and smooth muscle cell presence and function in the graft, with a presumed outcome of reduced maladaptive neointimal overgrowth, though early prevention of thrombosis is also a rationale.…”
Section: Graft Ec Integritymentioning
confidence: 99%